Pharmaceutical Production - An Engineering Guide - Bennett, Bill (Institution of Chemical Engineers, 2011)
This book is a general introduction aimed at all those involved in the engineering stages required for the manufacture of the active ingredient (drugs - primary manufacture) and its dosage forms (secondary manufacture).